Technologies and education in the context of five Latin American countries - Leguizamón González, Myriam Cecilia; Universidad Pedagógica y Tecnológica de Colombia; Díaz Bernal, Juan Guillermo; Universidad Pedagógica y Tecnológica de Colombia; Saavedra Bautista, Claudia Esperanza; Universidad Pedagógica y Tecnológica de Colombia; Ortiz Ortiz, Mary Luz; Universidad Pedagógica y Tecnológica de Colombia; Hernández Matta, María Rita; Universidad Pedagógica y Tecnológica de Colombia; Patiño Cuervo, Daniela; Universidad Pedagógica y Tecnológica de Colombia; Medina Carreño, Sandra Milena; Universidad Pedagógica y Tecnológica de Colombia; Ortega Iglesias, Jorge Mario; Universidad Pedagógica y Tecnológica de Colombia; Sandoval Espitia, Adriana; Universidad Pedagógica y Tecnológica de Colombia; Mejía Ortega, Iván Darío; Universidad Pedagógica y Tecnológica de Colombia; López López, Edgar Nelson; Universidad Pedagógica y Tecnológica de Colombia; Téllez Gómez, Angie Alejandra; Universidad Pedagógica y Tecnológica de Colombia; et al. (UPTC Editorial, 2022)
Scientific production in Latin America in relation to technology and information technology in education, offers an overview of what is happening in counterpart countries on the subject. This work presents the main research trends of the last 5 years at the level of 5 countries: Colombia, Argentina, Chile, Mexico and Venezuela, in order to interpret and collect the most relevant discourse in the 2015 - 2019 period. Determines to review the publications made in Latindex, systematize and analyze the information produced in the field under study. The book addresses in each chapter the conceptual categories: teacher training and TIC, educational technology, technology and society, virtual learning environments (VLE), teaching-learning, and ICT tools, through qualitative data analysis. This investigative process accounts for the stakes made by the countries under study, to bring ICTs to education, being evident  the use in parallel to the curriculum, articulated with political, infrastructure, economic, social and ethical issues, such as the most relevant.